Posisi al-Sunnah dalam Pemikiran Hukum al-Shafi’iy - Abu Azam Al Hadi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
This article discusses the view of al-Shafi’iy on al-Sunnah using historical analysis to uncover the significance of al-sunnah for al-Shafi’iy’s legal theory. This historical study is conducted by tracing al-Shafi’iy’s thought on the concept of al-sunnah in the period prior to him which Schacht labels as Ancient Schools of Law. Al-Shafi’iy had made radical change in understanding the concept of al-sunnah upheld by those early schools by criticizing the Ijma’ doctrines and limiting it to the aspects of basic r eligious duties. Al-Shafi’iy’s idea simply puts aside al-sunnah from the existing schools of law. For him, al-sunnah, which is transmitted from the Prophet in form of hadith though chains of trustworthy transmitters, is a source of Islamic law in its own right regardless whether it is widely accepted or otherwise. Further, it is remain a valid source even if it is only an isolated transmission (ahad).